2017
DOI: 10.3390/molecules22101688
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 11C-Labelled Ureas by Palladium(II)-Mediated Oxidative Carbonylation

Abstract: Positron emission tomography is an imaging technique with applications in clinical settings as well as in basic research for the study of biological processes. A PET tracer, a biologically active molecule where a positron-emitting radioisotope such as carbon-11 has been incorporated, is used for the studies. Development of robust methods for incorporation of the radioisotope is therefore of the utmost importance. The urea functional group is present in many biologically active compounds and is thus an attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Over the past years, different research groups have provided solutions to the problems of low solubility and concentration of [ 11 C ]CO in various ways. The standard protocols for the preparation of [ 11 C ]CO rely on the reduction of [ 11 C ]CO 2 with metallic zinc at 400°C or metallic molybdenum at 850°C . Even though the reduction is effective, the main challenge is to obtain an adequate trapping efficiency of [ 11 C ]CO into the reaction medium .…”
Section: Carbonylation Using [11c ]Comentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years, different research groups have provided solutions to the problems of low solubility and concentration of [ 11 C ]CO in various ways. The standard protocols for the preparation of [ 11 C ]CO rely on the reduction of [ 11 C ]CO 2 with metallic zinc at 400°C or metallic molybdenum at 850°C . Even though the reduction is effective, the main challenge is to obtain an adequate trapping efficiency of [ 11 C ]CO into the reaction medium .…”
Section: Carbonylation Using [11c ]Comentioning
confidence: 99%
“…The standard protocols for the preparation of [ 11 C ]CO rely on the reduction of [ 11 C ]CO 2 with metallic zinc at 400°C or metallic molybdenum at 850°C. [110][111][112] Even though the reduction is effective, the main challenge is to obtain an adequate trapping efficiency of [ 11 C ]CO into the reaction medium. 113 Early attempts relied on recirculation systems and the preconcentration of the generated [ 11 C] CO. 114 However, it was found that more technical solutions were necessary, leading to the development of SCHEME 31 A-B, Suggested decarbonylations supported by [ 13 C]CO-incorporation SCHEME 32 Chemical trapping of [ 11 C ]CO with borane tetrahydrofuran sophisticated techniques, including microfluidic systems, high-pressure microautoclaves, microtube reactors, and chemical trapping.…”
Section: Techniques For Converting [ 11 C ]Co 2 To [ 11 C]comentioning
confidence: 99%
“…Although [ 11 C]phosgene is highly reactive and has been widely used for [ 11 C]ureas synthesis (Roeda and Dollé 2010), the regular production of this [ 11 C]synthon is very challenging and tedious, and often provides low A m . Pd(II)-Mediated oxidative 11 C-carbonylation reactions between aliphatic or aromatic amines with [ 11 C]carbon monoxide have been explored recently for the synthesis of symmetrical and unsymmetrical [ 11 C]ureas (Roslin et al 2017) (Fig. 8, a).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the intrinsic complexity of the transition metal‐mediated chemistry, a high number of optimization reactions are commonly performed towards achieving satisfactory radiochemical yields . Also, when developing novel [ 11 C] CO chemistry, a small library of radiolabeled compounds with different functionalities needs to be generated, resulting in the execution of many reactions . Recently, various technical advances in [ 11 C] CO chemistry have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Also, when developing novel [ 11 C] CO chemistry, a small library of radiolabeled compounds with different functionalities needs to be generated, resulting in the execution of many reactions. 8,9 Recently, various technical advances in [ 11 C] CO chemistry have been reported. Besides alternative methods for producing [ 11 C]CO, [10][11][12] techniques have emerged that allow carbonylation reactions to be executed at near atmospheric pressure.…”
mentioning
confidence: 99%